Preaching of Islam - "Arnold, T.W." (Delhi, 1984)
This book is study of the phenomenal spread of Islam has tended to be dominated by historians who have assumed to have been a concomitant of the Muslims, political conquests. it reveals that Islam has won its spiritual conquests in places where its political power was lowest ebb. The work examines evidences to ascertain what were the political, economic, social-other than religious- motives that were manifested.
Keywords: Islam history